2020
DOI: 10.1021/acs.estlett.0c00019
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Living Filtration Membranes

Abstract: As demand for clean water increases, there is a growing need for effective sustainable water treatment systems. We used the symbiotic culture of bacteria and yeast (SCOBY) that forms while brewing kombucha tea as a living water filtration membrane (LFM). The LFMs function as ultrafiltration membranes with a permeability of 135 ± 25 L m–2 h–1 bar–1 and a 90% rejection of 30 nm nanoparticles. Because they contain living microorganisms that produce cellulose fibers, the surface of an LFM heals after a puncture or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 28 publications
0
39
0
1
Order By: Relevance
“…Ghimire, et al [89] presented a crucial estimation and perspective of two main pathways for promoting more sustainable and circular-economy-founded wastewater treatment and depicted that combining both concepts may lead to superior energy and resource efficiency for wastewater treatment systems Ghernaout, et al [90]; Ghernaout and Elboughdiri [91]; Ghernaout and Elboughdiri [92]. Eggensperger, et al [93] mentioned the usage of self-healing bacterially generated cellulose fiber networks producing sustainable biological membranes apt to filter water for potable water purposes. Bentel, et al [94] announced that alternative energy-efficient and sustainable remediation methods comprising the implementation of ultraviolet (UV)/sulfite water treatments could furnish efficient decay of persistent with perfluoroalkyl chemicals in raw water for onward potable water use.…”
Section: Sustainable Water Resourcesmentioning
confidence: 99%
“…Ghimire, et al [89] presented a crucial estimation and perspective of two main pathways for promoting more sustainable and circular-economy-founded wastewater treatment and depicted that combining both concepts may lead to superior energy and resource efficiency for wastewater treatment systems Ghernaout, et al [90]; Ghernaout and Elboughdiri [91]; Ghernaout and Elboughdiri [92]. Eggensperger, et al [93] mentioned the usage of self-healing bacterially generated cellulose fiber networks producing sustainable biological membranes apt to filter water for potable water purposes. Bentel, et al [94] announced that alternative energy-efficient and sustainable remediation methods comprising the implementation of ultraviolet (UV)/sulfite water treatments could furnish efficient decay of persistent with perfluoroalkyl chemicals in raw water for onward potable water use.…”
Section: Sustainable Water Resourcesmentioning
confidence: 99%
“…size cutoff). 4,39 Overview of LFM preparation and use; life cycle inventory data; simulation results for NaOHand H2O2-treated LFMs.…”
Section: Global Sensitivity Analysismentioning
confidence: 99%
“…LFMs have created a new category of water filtration technologies, as they are a biodegradable material that may be fabricated into virtually any shape from μm to mm dimensions, 16 and be structurally and chemically modified to impregnate anti-fouling 17,18 and/or diffusion properties. 4,19 A multitude of subsequent studies can be developed upon this proof of concept, e.g., permeability modifications, 11 functional modifications through incorporation of other molecules, [20][21][22] and optimization of the engineering design and operation conditions. 23 To integrate environmental considerations into future technology development (i.e., Ecodesign), 24,25 herein we conduct a preliminary life cycle assessment of LFMs as a drinking water filtration technology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that it is possible to encode light-induced, membrane-potential-based memory-patterns within bacteria in intimate contact as a biofilm [ 11 ]. Besides the noxious impact on food, water quality and health care industry, biofilms can serve as a useful and sustainable alternative to provide a low-cost source of power and clean sustainable energy or even act beneficially during cost-effective and sustainable water treatment procedures for some types of filters [ 12 ]. Nevertheless, the spread of contagious microorganisms and robust biofilm development is seen as a threat for human health and compromises the quality and performance of various man-made products.…”
Section: Introductionmentioning
confidence: 99%